Growth and electrical transport properties of InGaN/GaN heterostructures grown by PAMBE. (January 2015) - Sinha, Neeraj; Roul, Basanta; Mukundan, Shruti; Chandan, Greeshma; Mohan, Lokesh; Jali, V.M.; Krupanidhi, S.B.
Graphical abstract: Highlights: InGaN thin films were grown on GaN template by PAMBE. InGaN films were characterized by HRXRD, SEM and PL and Raman spectroscopy. The indium incorporation in single phase InGaN films was found to be 23%. The I – V characteristic of the InGaN/GaN heterojunction shows rectifying behavior. Log–log plot of the I – V characteristics indicates the presence of SCLC mechanism. Abstract: InGaN epitaxial films were grown on GaN template by plasma-assisted molecular beam epitaxy. The composition of indium incorporation in single phase InGaN film was found to be 23%. The band gap energy of single phase InGaN was found to be ∼2.48 eV. The current–voltage ( I – V ) characteristic of InGaN/GaN heterojunction was found to be rectifying behavior which shows the presence of Schottky barrier at the interface. Log–log plot of the I – V characteristics under forward bias indicates the current conduction mechanism is dominated by space charge limited current mechanism at higher applied voltage, which is usually caused due to the presence of trapping centers. The room temperature barrier height and the ideality factor of the Schottky junction were found to 0.76 eV and 4.9 respectively. The non-ideality of the Schottky junction may be due to the presence of high pit density and dislocation density in InGaN film.